Pieris brassicae inhibits xanthine oxidase. - Sousa, C. (2011)
The antioxidant potential of an aqueous extract obtained from Pieris brassicae larvae reared on Brassica oleracea L. var. costata DC was evaluated against 2,2-diphenyl-1-picrylhydrazyl radical and several reactive oxygen species. The results revealed an effective concentration-dependent protective activity against superoxide and hydroxyl radicals, being superior to that of the host plant. In addition, the larvae extract also exhibited a strong inhibitory effect on xanthine oxidase that was not observed for B. oleracea var. costata. A weak scavenging ability was noticed for hypochlorous acid. Several phenolic compounds with complex chemical structures that are hard to synthesize in the laboratory were found in P. brassicae extract. This is the first time that an insect has been tested for its xanthine oxidase inhibitory capacity, which proved to be very high. These findings are interesting considering that they can be used by food or pharmaceutical industries to prevent the oxidation of their products, to increase the dietary supply of antioxidants, or for prevention of free radical-mediated diseases, namely, gout.